An Empirical Approach to the Signalling of Enumerative Structures - Lydia-Mai Ho-Dac; Cécile Fabre; Marie-Paule Péry-Woodley; Josette Rebeyrolle; Ludovic Tanguy (Discours)
This paper presents a data-intensive study of the signalling of enumerative structures. In contrast with semasiological studies of specific markers, the approach described here takes as its starting point annotated structures and cues, seeking to identify recurrent patterns in these data. To do so, it exploits a new resource for French, the ANNODIS resource, a large corpus of written texts manually annotated at discourse level. The data analysed —first quantitatively with large populations, then qualitatively on selected examples— allows the authors to illustrate how cues involved in signalling text organisation combine in complex ways metadiscourse and propositional content, or the textual and ideational metafunctions.